Preparation method of low-rebound negative electrode sheet, negative electrode sheet and battery

CN122991972APending Publication Date: 2026-10-27HUIZHOU WES NEW ENERGY LIMITED
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611413924.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-11
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

但在锂电池生产过程中,石墨负极极片的辊压环节存在突出的技术缺陷:传统单级辊压易造成材料内部应力集中,卸压后厚度反弹可达5%-10%,导致极片厚度不均匀;高压辊压易破坏导电网络结构,降低电子传输效率;辊压过程中的粘辊现象还会引发极片表面微裂纹,造成循环性能衰减

Benefits of technology

1.材料体系优化:通过高低粘度复配CMC、高Tg改性SBR与PEO交联助剂组合,在石墨颗粒间构建致密三维交联粘结网络,从微观层面限制颗粒微滑移与重排,从本征上降低回弹的结构基础。对比传统单一粘度CMC体系,极片180°剥离强度提升至18.5N/m,涂层掉粉量降至0.08mg,粘结性能提升一倍以上,为低回弹辊压提供稳定的材料基底。

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The application discloses a preparation method of a low-rebound negative electrode sheet, a negative electrode sheet and a battery, and relates to the technical field of lithium battery production. In view of the problems of large rebound and poor thickness uniformity of a graphite negative electrode after rolling, the slurry system of the scheme adopts high and low viscosity compounded CMC, high Tg modified SBR and added PEO crosslinking aid, and the sheet is prepared by combining four-stage gradient constant-temperature drying and dehumidification slow cooling process, preheating at 30-40 DEG C, three-stage warm rolling with gradually increasing gradient, and matching soft and hard composite rolls and pressure maintaining extension section. The sheet rebound rate can be reduced to 2-3% after 24 hours of standing, the compaction density reaches 1.65-1.75 g / cm 3 , the thickness uniformity of the sheet and the cycle performance of the battery are significantly improved, and the scheme is suitable for high-compaction lithium battery manufacturing.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of battery manufacturing technology, and in particular to a method for preparing a low-rebound negative electrode, the negative electrode, and a battery. Background Technology

[0002] With the increasing demand for clean energy and efficient energy storage technologies, lithium batteries are widely used in electric vehicles, consumer electronics, and energy storage systems due to their high-performance energy storage characteristics. Graphite anodes, with their abundant resources, low price, and stable electrochemical performance, have become the most mainstream anode material for lithium batteries. However, the rolling process of graphite anode sheets in lithium battery production has significant technical defects: traditional single-stage rolling easily causes stress concentration within the material, resulting in a 5%-10% thickness rebound after pressure relief, leading to uneven electrode thickness; high-pressure rolling easily damages the conductive network structure, reducing electron transport efficiency; and the sticking phenomenon during rolling can also cause micro-cracks on the electrode surface, causing cycle performance degradation. These problems directly affect the battery's assembly accuracy, energy density, cycle life, and safety. Therefore, developing a low-rebound, high-pressure anode sheet preparation process is a pressing technical challenge in the lithium battery manufacturing field. Summary of the Invention

[0003] The purpose of this application is to provide a method for preparing a low-rebound negative electrode, a negative electrode, and a battery, so as to solve at least one of the above-mentioned technical problems.

[0004] In a first aspect, this application provides a method for preparing a low-rebound negative electrode sheet, the method comprising the following steps: S1. Prepare the negative electrode slurry. The thickener is a sodium carboxymethyl cellulose system with high and low viscosity. The binder is modified styrene-butadiene rubber with a high glass transition temperature. Add 0.1%-0.3% of polyethylene oxide crosslinking aid by mass of negative electrode active material to the negative electrode slurry. S2. After coating the negative electrode slurry onto the surface of the current collector, it is dried. The drying process adopts a four-stage gradient temperature control process, which involves sequentially increasing the temperature to 80-90℃, 100-110℃, and 115-125℃, and then baking at a constant temperature of 110℃ for 5-15 minutes. After drying, the electrode is dehumidified and slowly cooled. S3. Before rolling, the electrode sheet is preheated at a temperature of 30-40℃ for 1-3 minutes to ensure uniform temperature across the entire electrode sheet. S4. After preheating, the electrode sheet undergoes gradient rolling in a pre-pressing section, an intermediate pressing section, and a fine pressing section, with the roller temperature and pressure increasing progressively. Specifically, the pre-pressing section has a roller temperature of 40℃ and a pressure of 8-12 MPa; the intermediate pressing section has a roller temperature of 50℃ and a pressure of 15-20 MPa; and the fine pressing section has a roller temperature of 55℃ and a pressure of 2226 MPa. The fine pressing section employs a composite roller structure consisting of a hard work roller and an elastic buffer back roller, and is equipped with a roller table pressure-maintaining extension section. After rolling, the compacted density of the electrode sheet is 1.65-1.75 g / cm³. 3 .

[0005] Preferably, in step S1, the mass ratio of high viscosity CMC to low viscosity CMC in the high-low viscosity CMC compound system is 7:3. The high-viscosity CMC has a viscosity of 1200-1500 mPa·s, and the low-viscosity CMC has a viscosity of 300-600 mPa·s.

[0006] Preferably, in step S1, the glass transition temperature of the modified styrene-butadiene rubber (SBR) is -10℃ to 0℃; the mass ratio of the CMC to the SBR is 1:(1.2-1.8).

[0007] Preferably, in step S1, the amount of PEO crosslinking aid added is 0.2% of the mass of the negative electrode active material; the solid content of the negative electrode slurry is 54%, and the slurry viscosity is controlled at 4000 mPa·s.

[0008] Preferably, in step S2, the temperatures of each segment of the four-segment gradient temperature control process are 85℃, 105℃, 120℃, and 110℃ respectively, wherein the constant temperature baking time at 110℃ is 5 minutes.

[0009] Preferably, in step S3, the preheating of the roller is achieved through a constant temperature preheating channel, with a preheating temperature of 35°C and a preheating time of 2 minutes.

[0010] Preferably, in step S4, the roller speed of the pre-pressing section is 8-10 m / min, and the thickness compression rate is 35%-40%; the roller speed of the intermediate pressing section is 6-8 m / min, and the thickness compression rate is 30%-35%; the roller speed of the fine pressing section is 4-6 m / min.

[0011] Preferably, the pressure-holding extension section of the roller conveyor is located on the discharge side of the fine pressing section. After the electrode sheet is finely pressed, it enters the pressure-holding extension section to maintain the pressure state, so as to suppress the instantaneous rebound after roller pressing.

[0012] Secondly, this application provides a negative electrode sheet, which is prepared by the preparation method described in the first aspect of this application.

[0013] Thirdly, this application provides a battery comprising the negative electrode sheet described in the second aspect of this application.

[0014] Compared with the prior art, this application includes at least the following technical effects: 1. Material System Optimization: By combining high- and low-viscosity CMC, high-Tg modified SBR, and PEO crosslinking aids, a dense three-dimensional crosslinked bonding network is constructed between graphite particles. This restricts particle microslippage and rearrangement at the microscopic level, intrinsically reducing the structural basis for springback. Compared with the traditional single-viscosity CMC system, the electrode 180° peel strength is increased to 18.5 N / m, the coating powder loss is reduced to 0.08 mg, and the bonding performance is more than doubled, providing a stable material substrate for low-springback rolling.

[0015] 2. Optimized Drying Process: A four-stage gradient heating process combined with end-stage constant-temperature baking and slow cooling via dehumidification achieves orderly solvent evaporation and gradual coating curing. This effectively eliminates internal stress during coating curing, prevents micro-stress cracks caused by sudden cooling of the electrode, and reduces the sources of internal stress leading to long-term rebound. Compared to a three-stage drying process without constant temperature control, this process can reduce the long-term rebound rate by approximately 2 percentage points after 72 hours of standing, stabilizing the rebound rate at 2%-3%.

[0016] 3. Preheating effect before rolling: Preheating before rolling at 30-40℃ moderately softens the binder system, enhances the plastic deformation ability of graphite particles and binder, and reduces stress concentration during rolling. This process can independently contribute 1.5-2.0 percentage points to the reduction in springback rate, while improving the overall temperature uniformity of the electrode and reducing local springback differences.

[0017] 4. Gradient Rolling Effect: A three-stage, progressively increasing temperature and pressure gradient rolling process, combined with soft-hard composite rolls and a pressure-holding extension section, achieves gradual compaction and stress release of the electrode sheet, suppressing instantaneous high-pressure rebound. Ultimately, the rebound rate of the electrode sheet after 24 hours of resting drops to 2.5%, far lower than the 8.2% of traditional processes; the compaction density reaches 1.70 g / cm³. 3 Compared with the basic value of the same material, it is 8%-12% higher; the maximum deviation of in-plane thickness is narrowed to ±1.2μm, and the dimensional accuracy is significantly improved.

[0018] 5. Improved electrochemical performance: The battery prepared using the electrode sheet of this scheme has an electrode sheet thickness expansion rate of only 8.5% when fully charged, which is lower than 11.5% of the traditional process; the capacity retention rate of 300 cycles of 1C charge and discharge at 25℃ reaches 92.3%, which is 8.8 percentage points higher than 83.5% of the traditional process, effectively extending the battery cycle life and improving the reliability of use. Detailed Implementation

[0019] To make the objectives, features, and advantages of the present invention more apparent and understandable, the specific embodiments of the present invention are described in detail below with reference to examples. Several embodiments of the present invention are given below. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. Rather, these embodiments are provided so that the disclosure of the present invention will be more thorough and complete: This application provides a method for preparing a negative electrode sheet with low rebound, which includes the following steps: S1. Prepare the negative electrode slurry. The thickener is a sodium carboxymethyl cellulose system with high and low viscosity. The binder is modified styrene-butadiene rubber with a high glass transition temperature. Add 0.1%-0.3% of polyethylene oxide crosslinking aid by mass of negative electrode active material to the negative electrode slurry. S2. After coating the negative electrode slurry onto the surface of the current collector, it is dried. The drying process adopts a four-stage gradient temperature control process, which involves sequentially increasing the temperature to 80-90℃, 100-110℃, and 115-125℃, and then baking at a constant temperature of 110℃ for 5-15 minutes. After drying, the electrode is dehumidified and slowly cooled. S3. Before rolling, the electrode sheet is preheated at a temperature of 30-40℃ for 1-3 minutes to ensure uniform temperature across the entire electrode sheet. S4. After preheating, the electrode sheet undergoes gradient rolling in a pre-pressing section, an intermediate pressing section, and a fine pressing section, with the roller temperature and pressure increasing progressively. Specifically, the pre-pressing section has a roller temperature of 40℃ and a pressure of 8-12 MPa; the intermediate pressing section has a roller temperature of 50℃ and a pressure of 15-20 MPa; and the fine pressing section has a roller temperature of 55℃ and a pressure of 2226 MPa. The fine pressing section employs a composite roller structure consisting of a hard work roller and an elastic buffer back roller, and is equipped with a roller table pressure-maintaining extension section. After rolling, the compacted density of the electrode sheet is 1.65-1.75 g / cm³. 3 .

[0020] In this solution, on the material side, a combination of high- and low-viscosity CMC, high-Tg modified SBR, and PEO crosslinking aids is used to construct a dense three-dimensional crosslinked bonding network between graphite particles. This restricts particle microslippage and rearrangement at the microscopic level, intrinsically reducing the structural basis for springback. On the drying side, a four-stage gradient heating process combined with end-stage isothermal cooling and dehumidification achieves orderly solvent evaporation and gradual coating curing, effectively eliminating internal stress in the coating, preventing microcracks caused by sudden cooling, and reducing the source of internal stress for long-term springback. At the front end of the roll forming process, 30- Preheating at 40℃ softens the binder to a moderate degree, reducing stress concentration during rolling. At the rolling end, a gradient rolling process with progressively increasing temperature and pressure, combined with soft and hard composite rolls and a pressure-holding extension section, achieves gradual stress release and suppresses instantaneous high-pressure rebound. Compared with traditional mass production processes, this process can reduce the rebound rate of the electrode sheet after 24 hours of rest to a low level, reduce the maximum in-plane thickness deviation, improve compaction density, and simultaneously improve the capacity retention rate after 300 cycles. It achieves a multiple balance between high compaction, low rebound, and long cycling, significantly improving battery assembly accuracy and electrochemical performance.

[0021] In some embodiments, in step S1, the mass ratio of high viscosity CMC to low viscosity CMC in the high-low viscosity CMC blend system is 7:3. Among them, the viscosity of high viscosity CMC is 1200-1500 mPa·s, and the viscosity of low viscosity CMC is 300-600 mPa·s; In this design, the high-viscosity component provides stronger suspension and thickening capabilities, effectively preventing graphite particle sedimentation and ensuring the uniformity of solid content and viscosity of the slurry during long-term storage. The low-viscosity component improves the slurry's flow properties, reduces resistance during coating, and minimizes areal density deviation and surface streaks. The 7:3 blending ratio represents an experimentally verified optimal balance: if the high-viscosity component is too high, the slurry viscosity becomes excessive, increasing coating resistance and making orange peel defects more likely; if the low-viscosity component is too high, the slurry's suspension is insufficient, leading to particle sedimentation and uneven longitudinal thickness. When this blended system works synergistically with the SBR binder, it forms a more uniformly distributed adhesive network. Compared to a single-viscosity CMC system, the 180° peel strength of the electrode can be increased by more than 60%, while reducing localized rebound differences caused by uneven binder distribution during rolling. This provides a stable material substrate for low-rebound rolling, further improving the overall thickness uniformity of the electrode.

[0022] In some embodiments, in step S1, the glass transition temperature of the modified styrene-butadiene rubber (SBR) is -10°C to 0°C; the mass ratio of CMC to SBR is 1:(1.2-1.8). In this scheme, high-Tg modified SBR, compared with traditional low-Tg styrene-butadiene rubber, has higher cohesive strength and elastic modulus at room temperature. After roll pressing and decompression, it can provide stronger anti-rebound cohesive force and reduce the elastic recovery of the binder itself. At the same time, this Tg range is precisely matched with the roll pressing temperature range (40-55℃). When the roll pressing temperature rises, the SBR softens appropriately, which ensures the compliance of compression deformation and avoids surface quality problems such as sticking to the roller and powdering due to excessive viscoelasticity. CMC and SBR are compounded at a mass ratio of 1:(1.2-1.8), which realizes the interpenetration matching of the thickening network and the bonding network: the hydroxyl groups of CMC and SBR particles form a stable interpenetrating structure, which ensures the adhesion and flexibility of the coating and avoids the increase of electrode internal resistance and elastic rebound caused by excessive SBR.

[0023] In some embodiments, in step S1, the amount of PEO crosslinking aid added is 0.2% of the mass of the negative electrode active material; the solid content of the negative electrode slurry is 54%, and the slurry viscosity is controlled at 4000 mPa·s; In this scheme, the addition of 0.2% polyethylene oxide crosslinking aid can form a three-dimensional physical crosslinking network in the micro-interstices of graphite particles. This network restricts the micro-slippage and rearrangement of graphite particles after pressure relief through molecular chain entanglement and binding, suppressing roll springback at the microstructural level. This is one of the core material mechanisms for reducing springback in this scheme. Insufficient PEO crosslinking aid results in an incomplete crosslinking network and limited effect in suppressing particle slippage; excessive addition increases the ionic and electronic internal resistance of the electrode, deteriorating electrochemical performance. Simultaneously, a solid content of 54% and a viscosity of 4000 mPa·s represent the optimal process window for the aforementioned high- and low-viscosity CMC compound system, ensuring high coating efficiency, reducing drying energy consumption and solvent usage, while avoiding poor slurry flowability, coating streaks, and thick edge defects caused by excessive solid content.

[0024] In some implementations, in step S2, the temperatures of each segment of the four-segment gradient temperature control process are 85°C, 105°C, 120°C, and 110°C, respectively, with the constant temperature baking time at 110°C being 5 minutes.

[0025] In this scheme, during the first three stages of gradient heating, the solvent diffuses smoothly from the inside of the coating to the surface, avoiding surface skinning, internal solvent residue, and pinhole defects caused by rapid heating, thus ensuring a uniform and dense coating structure. The final 110°C constant temperature baking can further eliminate the internal stress generated during the coating curing process, making the adhesive migration and distribution more uniform and improving the stability of the coating structure.

[0026] In some embodiments, in step S3, the preheating of the roller is achieved through a constant temperature preheating channel, with a preheating temperature of 35°C and a preheating time of 2 minutes. This solution limits preheating before rolling to a constant-temperature preheating channel, with a preheating temperature of 35℃ and a preheating time of 2 minutes. This is a crucial buffer process connecting drying and rolling, achieving improved electrode plasticity and reduced stress through precise temperature and time control. The 35℃ preheating temperature precisely matches the glass transition range of high-Tg SBR, allowing for appropriate softening of the binder system, enhancing the plastic deformation capacity of graphite particles and binder, reducing yield strength and elastic strain energy storage during rolling, and preventing SBR sticking to the rollers and electrode surface contamination due to excessive temperature.

[0027] A 2-minute preheating time ensures that the electrode temperature is uniform from the surface to the core, avoiding problems such as inconsistent deformation and large differences in local rebound caused by temperature differences between the surface and the interior.

[0028] In some embodiments, in step S4, the roller speed of the pre-pressing section is 8-10 m / min, and the thickness compression rate is 35%-40%; the roller speed of the intermediate pressing section is 6-8 m / min, and the thickness compression rate is 30%-35%; the roller speed of the fine pressing section is 4-6 m / min. This scheme limits the roller speed and thickness compression ratio of each stage of the three-stage gradient rolling process: the pre-compression stage has a roller speed of 8-10 m / min and a compression ratio of 35%-40%; the intermediate compression stage has a roller speed of 6-8 m / min and a compression ratio of 30%-35%; and the fine compression stage has a roller speed of 4-6 m / min. Through the design of gradually reducing the speed and distributing the compression amount in stages, combined with the gradually increasing roller temperature and pressure, the electrode sheet is gradually compacted and the stress is gradually released, avoiding stress concentration and violent rebound caused by a single large compression amount.

[0029] The pre-pressing section employs a high roller speed and a large initial compression ratio to quickly achieve preliminary densification of the electrode sheet, expel most of the air inside the coating, establish basic compaction, and ensure overall production efficiency. The intermediate pressing section uses a medium roller speed and compression ratio to further increase compaction density while allowing sufficient stress release time to reduce the accumulation of elastic strain energy. The fine pressing section uses a lower roller speed to extend the residence time of the electrode sheet in the high-pressure zone, allowing for more thorough particle rearrangement and more uniform compaction. This combination of parameters ensures the production capacity of the rolling process while reducing the elastic strain energy of each stage through step-by-step deformation. The total rebound after depressurization is significantly lower than that of a single large-pressure process. At the same time, it avoids electrode sheet wrinkling, roller sticking, and edge warping caused by high speed and high pressure, improving the dimensional accuracy and surface quality of the electrode sheet.

[0030] In some embodiments, the pressure holding extension section of the roller conveyor is located on the discharge side of the fine pressing section. After the electrode sheet is finely pressed, it enters the pressure holding extension section to maintain the pressure state in order to suppress the instantaneous rebound after roller pressing. In traditional roll forming processes, the pressure is suddenly released the instant the electrode leaves the roll, and the elastic strain energy stored inside the coating is released rapidly, resulting in a significant instantaneous thickness rebound. However, the pressure holding extension section can maintain a continuous clamping pressure after the electrode leaves the work roll, extending the stress release time window, allowing the plastic deformation of the binder and graphite particles to be more complete, and gradually releasing the elastic strain energy, thereby significantly reducing the instantaneous rebound.

[0031] The following are some specific examples. When %, it refers to a percentage by weight. It should be noted that the following examples do not exhaustively list all possible scenarios, and the materials used in the following examples are commercially available unless otherwise specified; the process steps and parameters involved are performed according to conventional process conditions in the art unless otherwise specified. Example 1

[0032] This embodiment describes the standard preparation process for a low-rebound, high-voltage negative electrode sheet. The specific steps are as follows: (1) Slurry preparation Natural graphite is used as the negative electrode active material, and SP is used as the conductive agent. The total amount of binder added is 2.0% of the mass of the negative electrode active material. Among them, sodium carboxymethyl cellulose (CMC) adopts a high-low viscosity compound system, with a mass ratio of high viscosity CMC to low viscosity CMC of 7:3. The viscosity of high viscosity CMC is 1200-1500 mPa·s, and the viscosity of low viscosity CMC is 300-600 mPa·s. The total amount of CMC added is 0.8%. Styrene-butadiene rubber (SBR) adopts high Tg modified styrene-butadiene rubber with a glass transition temperature of -5℃, and the amount added is 1.2%. The mass ratio of CMC to SBR is 1:1.5.

[0033] Add 0.2% (by mass) of polyethylene oxide (PEO) crosslinking agent to the negative electrode slurry to fill the micro-gaps between graphite particles and construct a dense three-dimensional crosslinked bonding network; adjust the solid content of the negative electrode slurry to 54% and control the slurry viscosity to 4000 mPa·s.

[0034] (2) Coating and drying The prepared negative electrode slurry is evenly coated on the surface of the copper foil current collector and dried using a four-stage gradient temperature control process: the temperature is set to gradually increase to 85℃, 105℃, and 120℃, and finally baked at a constant temperature of 110℃ for 5 minutes. After drying, the electrode is discharged through a dehumidification and slow cooling transition section to control the weight loss ratio of the electrode to be less than 0.1% and avoid micro-stress cracks caused by sudden cooling of the electrode.

[0035] (3) Preheating before rolling Before entering the rolling process, the dried electrode sheets are preheated in a 35°C constant temperature preheating channel for 2 minutes to ensure uniform temperature throughout the electrode sheets and moderately soften the electrode material, making it better adaptable to rolling deformation.

[0036] (4) Three-stage gradient temperature and pressure roller pressing After preheating, the electrode sheets undergo gradient rolling in a pre-pressing section, an intermediate pressing section, and a fine pressing section. The rolling temperature and rolling pressure increase progressively in each section to achieve gradual stress release. - Pre-compression section: Roller temperature 40℃, roller pressure 10MPa, roller speed 9m / min, thickness compression rate 38%, completes the initial densification of the electrode sheet and removes most of the air inside the coating; - Medium pressure section: Roller temperature 50℃, roller pressure 18MPa, roller speed 7m / min, thickness compression rate 33%, further improving compaction density, while reserving stress release time; - Precision pressing section: Roller temperature 55℃, roller pressure 24MPa, roller speed 5m / min; The precision pressing section adopts a composite roller structure of hard working roller and elastic buffer back roller, and a roller pressure holding extension section is set on the discharge side of the precision pressing section. After the electrode is precision pressed, it enters the pressure holding extension section to maintain the pressure state, which greatly suppresses the instantaneous rebound under high pressure.

[0037] After rolling, the compacted density of the electrode sheet is 1.70 g / cm³. 3 . Example 2

[0038] The negative electrode preparation process in this embodiment is basically the same as that in Example 1, except that: the mass ratio of CMC to SBR is 1:1.2, the amount of PEO crosslinking aid added is 0.1% of the mass of the negative electrode active material, and the constant temperature baking time at 110℃ in the four-stage gradient drying is 8 minutes. Example 3

[0039] The negative electrode preparation process in this embodiment is basically the same as that in Example 1, except that: the mass ratio of CMC to SBR is 1:1.8, the amount of PEO crosslinking aid added is 0.3% of the mass of the negative electrode active material, and the constant temperature baking time at 110℃ in the four-stage gradient drying is 15 min. Gradient Validation Example

[0040] To verify the optimal range and boundaries of each process parameter of the present invention and to verify the universality of the process, based on Example 1, only the corresponding single variable was changed, while the rest of the formula and process parameters were completely consistent with Example 1, and the following gradient verification groups were set. Roller temperature gradient group

[0041] Example 4: Pre-pressing section roller temperature 35℃, intermediate pressing section roller temperature 45℃, fine pressing section roller temperature 50℃; the remaining processes and formulas are the same as in Example 1.

[0042] Example 5: That is, Example 1, with the pre-pressing section roller temperature at 40°C, the intermediate pressing section roller temperature at 50°C, and the fine pressing section roller temperature at 55°C.

[0043] Example 6: Pre-pressing section roller temperature 45℃, intermediate pressing section roller temperature 55℃, fine pressing section roller temperature 60℃; the remaining processes and formulas are the same as in Example 1.

[0044] The verification results show that when the roller temperature is below 40℃, the binder is not softened enough, the internal stress of the coating is not fully released, and the rebound rate increases after pressure relief. The rebound rate of the low-temperature group after standing for 24 hours is about 4.5%. When the roller temperature is above 55℃, the SBR viscoelasticity is too strong, which easily leads to roller sticking and electrode powder shedding, resulting in a decrease in electrode surface quality. The amount of powder shedding increases significantly in the high-temperature group. The electrode rebound rate is the lowest in the 40-55℃ range and can be stabilized at 2-3%. Roller pressure gradient group

[0045] Example 7: Pre-compression stage pressure 8MPa, intermediate stage pressure 15MPa, fine compression stage pressure 22MPa; the remaining processes and formulas are the same as in Example 1.

[0046] Example 8: That is, Example 1, with a pre-compression pressure of 10 MPa, a medium-compression pressure of 18 MPa, and a fine-compression pressure of 24 MPa.

[0047] Example 9: Pre-compression stage pressure 12MPa, intermediate stage pressure 20MPa, fine compression stage pressure 26MPa; the remaining processes and formulations are the same as in Example 1.

[0048] Pressure gradient verification results show that when the pressure is below the range of 8-12 / 15-20 / 22-26 MPa, the electrode has insufficient compactness and high porosity, with a compacted density of only about 1.58 g / cm³. 3 The rebound rate increases; when the pressure is higher than this range, the instantaneous rebound intensifies and the conductive network is damaged, and the rebound rate of the high-voltage group rises to about 3.8%. Preheating gradient group before rollers

[0049] Example 10: The 35°C constant temperature preheating channel is eliminated, and the electrode directly enters the rolling process; the remaining processes and formulas are the same as in Example 1.

[0050] Example 11: Preheating temperature 30℃, holding time 2min; the rest of the process and formula are the same as in Example 1.

[0051] Example 12: That is, Example 1, with a preheating temperature of 35°C and a holding time of 2 minutes.

[0052] Example 13: Preheating temperature 40℃, holding time 2min; the rest of the process and formula are the same as in Example 1.

[0053] The preheating gradient verification results show that: preheating at 30-40℃ can soften the electrode material and reduce the concentration of rolling stress; when the preheating temperature is below 30℃, the improvement in springback rate is limited, and the springback rate of the group without preheating is about 4.8%; when the preheating temperature is above 40℃, the risk of sticking to the roller increases; the contribution of the 30-40℃ range to the springback rate is about 1.5-2.0 percentage points. Baking process control group

[0054] Example 14: The coating drying process adopts a three-stage heating process of 80-90℃, 100-110℃, and 115-125℃, and no constant temperature baking is set at the end; the rest of the process and formula are the same as in Example 1.

[0055] Example 15: That is, Example 1, using four-stage gradient temperature control at 85℃, 105℃, 120℃ and 110℃, with a constant temperature of 110℃ for 5 minutes at the end.

[0056] Example 16: In the four-stage gradient drying process, the final constant temperature baking time at 110°C is 15 minutes; the remaining processes and formulas are the same as in Example 1. The results of the baking comparison verification show that the end constant temperature baking is crucial to eliminating the internal stress of the coating. The group without constant temperature baking has a high rebound rate due to residual internal stress, and the rebound rate after standing for 72 hours is about 4.2%. The rebound rate of the group with constant temperature baking for 5-15 minutes is stable at 2-3%.

[0057] The following comparative examples were set up. Each comparative example used the same batch of raw materials, the same coating and rolling equipment, and the same testing conditions as the examples. Comparative Example 1

[0058] The traditional mass production process for negative electrode sheets is adopted: using a single viscosity CMC and conventional SBR formulation, a conventional single baking process, no preheating treatment before rolling, and a single-roll rolling process. Comparative Example 2

[0059] Only the ratio of CMC to SBR was optimized; the rest of the processes were the same as those in Comparative Example 1, using traditional mass production processes. Comparative Example 3

[0060] Only a three-stage gradient rolling process is used; the remaining formulation, baking, and preheating processes all use traditional mass production processes, consistent with Comparative Example 1. Comparative Example 4

[0061] Meanwhile, an optimized CMC / SBR ratio and a three-stage gradient rolling process are adopted, but no end-stage constant temperature baking or preheating before rolling is set; the rest of the process is the same as Comparative Example 1. Comparative Example 5

[0062] The formulation does not contain PEO crosslinking aids, and the rest of the formulation and process are exactly the same as in Example 1. Comparative Example 6

[0063] The 35°C constant temperature preheating channel was removed, and the rest of the formula and process were exactly the same as in Example 1. Comparative Example 7

[0064] The conventional three-stage heating and drying process is adopted, and the material is discharged after natural cooling. There is no end-stage constant temperature baking and dehumidification slow cooling. The rest of the formula and process are exactly the same as those in Example 1. Comparative Example 8

[0065] The fine pressing section uses ordinary rigid work rollers and does not have a roller conveyor pressure holding extension section; the rest of the formula and process are exactly the same as in Example 1. Comparative Example 9

[0066] The solution adopts the publicly available industry standard of "two-stage gradient rolling + conventional CMC / SBR formulation", which involves two-stage rolling, no PEO added, conventional baking process, and no preheating before rolling. Experimental test results and verification

[0067] The negative electrode sheets and corresponding batteries prepared in the above embodiments and comparative examples were subjected to performance tests, and the test methods are as follows: 1. Rebound rate after 24 hours of standing: The thickness t0 is measured immediately after the electrode is depressurized by the roller, and the thickness t∞ is measured after standing at room temperature for 24 hours. Rebound = (t∞−t0) / t0×100%.

[0068] 2. Electrode thickness expansion rate under full charge: The electrode is prepared into a full cell, and after being fully charged at 4.2V, it is disassembled and the thickness is measured. The expansion rate = (full charge thickness − initial thickness) / initial thickness × 100%.

[0069] 3. In-plane thickness uniformity (maximum deviation): The thickness of a single electrode is measured at 9 points, and the maximum thickness deviation value is recorded.

[0070] 4.180° Peel Strength: In accordance with GB / T 2792 standard, a 180° peel test was conducted at a test speed of 300 mm / min.

[0071] 5. Coating powder shedding: After applying 3M tape to the surface of the electrode, peel it off and weigh the mass of the powder that fell off.

[0072] 6. 1C capacity retention after 300 cycles: Under constant temperature of 25℃ and voltage range of 2.8-4.2V, the capacity retention rate is calculated as: discharge capacity at 300th cycle / discharge capacity at first cycle × 100%. Test results: Table 1

[0073] Example 1 2.70% 12.28% 92.5% Example 2 2.76% 13.30% 91.6% Example 3 2.82% 15.29% 91.7% Comparative Example 1 9.51% 25.62% 81.3% Comparative Example 2 7.21% 19.15% 83.2% Comparative Example 3 6.87% 21.89% 86.5% Comparative Example 4 6.31% 16.53% 88.7% Table 2

[0074] Rebound rate after 24 hours of standing Thickness was measured after roller pressing and standing at room temperature for 24 hours. 2.5% 8.2% 5.1% 4.8% 4.3% 3.8% 6.8% Electrode thickness expansion rate in full charge state Thickness measured after full charge at 4.2V 8.5% 11.5% 10.5% 10.2% 10.0% 9.4% 11.0% In-plane thickness uniformity (maximum deviation) Maximum deviation of thickness measured at 9 points on a single piece ±1.2μm ±4.5μm ±2.8μm ±2.5μm ±2.3μm ±2.0μm ±3.6μm 180° peel strength GB / T 2792, 300mm / min 18.5 N / m 9.2 N / m 12.3 N / m 14.0 N / m 15.0 N / m 15.5 N / m 10.5 N / m Coating powder shedding Weighing after applying 3M tape 0.08 mg 0.45 mg 0.22 mg 0.18 mg 0.15 mg 0.13 mg 0.35 mg 300 cycles 1C capacity retention 25℃、2.8-4.2V、 92.3% 83.5% 87.1% 88.0% 88.6% 89.8% 85.2% It should be noted that, unless otherwise specified, the embodiments and features described in this application can be combined with each other.

[0075] The above description is merely a preferred embodiment of this application and is not intended to limit this application in any way. Any simple modifications, equivalent changes, and alterations made to the above embodiments based on the technical essence of this application shall fall within the scope of the technical solution of this application.

Claims

1. A method for preparing a low-rebound negative electrode sheet, characterized in that: The preparation method includes the following steps: S1. Prepare the negative electrode slurry. The thickener is a sodium carboxymethyl cellulose system with high and low viscosity. The binder is modified styrene-butadiene rubber with a high glass transition temperature. Add 0.1%-0.3% of polyethylene oxide crosslinking aid by mass of negative electrode active material to the negative electrode slurry. S2. After coating the negative electrode slurry onto the surface of the current collector, it is dried. The drying process adopts a four-stage gradient temperature control process, which involves sequentially increasing the temperature to 80-90℃, 100-110℃, and 115-125℃, and then baking at a constant temperature of 110℃ for 5-15 minutes. After drying, the electrode is dehumidified and slowly cooled. S3. Before rolling, the electrode sheet is preheated at a temperature of 30-40℃ for 1-3 minutes to ensure uniform temperature across the entire electrode sheet. S4. After preheating, the electrode sheet undergoes gradient rolling in a pre-pressing section, an intermediate pressing section, and a fine pressing section, with the roller temperature and pressure increasing progressively. Specifically, the pre-pressing section has a roller temperature of 40℃ and a pressure of 8-12 MPa; the intermediate pressing section has a roller temperature of 50℃ and a pressure of 15-20 MPa; and the fine pressing section has a roller temperature of 55℃ and a pressure of 2226 MPa. The fine pressing section employs a composite roller structure consisting of a hard work roller and an elastic buffer back roller, and is equipped with a roller table pressure-maintaining extension section. After rolling, the compacted density of the electrode sheet is 1.65-1.75 g / cm³. 3 .

2. The preparation method according to claim 1, characterized in that: In step S1, the mass ratio of high viscosity CMC to low viscosity CMC in the high-low viscosity CMC compound system is 7:

3. The high-viscosity CMC has a viscosity of 1200-1500 mPa·s, and the low-viscosity CMC has a viscosity of 300-600 mPa·s.

3. The preparation method according to claim 1, characterized in that: In step S1, the glass transition temperature of the modified styrene-butadiene rubber (SBR) is -10℃ to 0℃; the mass ratio of CMC to SBR is 1:(1.2-1.8).

4. The preparation method according to claim 1, characterized in that: In step S1, the amount of PEO crosslinking aid added is 0.2% of the mass of the negative electrode active material; the solid content of the negative electrode slurry is 54%, and the slurry viscosity is controlled at 4000 mPa·s.

5. The preparation method according to claim 1, characterized in that: In step S2, the temperatures of each segment of the four-segment gradient temperature control process are 85℃, 105℃, 120℃, and 110℃ respectively, with the constant temperature baking time at 110℃ being 5 minutes.

6. The preparation method according to claim 1, characterized in that: In step S3, the preheating of the roller is achieved through a constant temperature preheating channel, with a preheating temperature of 35°C and a preheating time of 2 minutes.

7. The preparation method according to claim 1, characterized in that: In step S4, the roller speed of the pre-pressing section is 8-10 m / min, and the thickness compression rate is 35%-40%; the roller speed of the intermediate pressing section is 6-8 m / min, and the thickness compression rate is 30%-35%; the roller speed of the fine pressing section is 4-6 m / min.

8. The preparation method according to claim 1, characterized in that: The pressure-holding extension section of the roller conveyor is located on the discharge side of the fine pressing section. After the electrode sheet is finely pressed, it enters the pressure-holding extension section to maintain the pressure state, so as to suppress the instantaneous rebound after roller pressing.

9. A negative electrode sheet, characterized in that: It is prepared by the preparation method according to any one of claims 1-8.

10. A battery, characterized in that: It includes the negative electrode sheet as described in claim 9.